Influence of the nacnac Ligand in Iron(I)‐Mediated P4 Transformations. Issue 13 (29th February 2016) - Spitzer, Fabian; Graßl, Christian; Balázs, Gábor; Zolnhofer, Eva M.; Meyer, Karsten; Scheer, Manfred
Abstract: A study of P4 transformations at low‐valent iron is presented using β‐diketiminato (L) Fe I complexes [LFe(tol)] (tol=toluene; L=L 1 (1 a ), L 2 (1 b ), L 3 (1 c )) with different combinations of aromatic and backbone substituents at the ligand. The products [(LFe)4 (μ4 ‐η 2 :η 2 :η 2 :η 2 ‐P8 )] (L=L 1 (2 a ), L 2 (2 b )) containing a P8 core were obtained by the reaction of1 a, b with P4 in toluene at room temperature. Using a slightly more sterically encumbered ligand in1 c results in the formation of [(L 3 Fe)2 (μ‐η 4 :η 4 ‐P4 )] (2 c ), possessing a cyclo‐P4 moiety. Compounds2 a –c were comprehensively characterized and their electronic structures investigated by SQUID magnetization and 57 Fe Mössbauer spectroscopy as well as by DFT methods. Abstract : Depending on the size of the substituents of the N, N ′‐diarylated β‐diketiminato ligands, iron(I) complexes activate white phosphorus in different ways. Small substituents result in dimerization with formation of a realgar‐like P8 ligand at the center of a tetranuclear complex; larger substituents lead to planarization in dinuclear cyclo ‐P4 complexes.